Analisis Tingkat Kepuasan Kerja Karyawan di UD.Padma Sari - PRADNYANA, A.A.WAHYU; HANDAYANI, M. TH.; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.2, No.3, Juli 2013, 2013)
ABSTRACT Analysis of Employee Satisfaction on UD . Padma Sari The objective to be attained from this research is to find out the level of work satisfaction of employees of UD. Padma Sari working for more than three years and less than three years. The determination of the location is conducted by using purposive method, namely, a method which is intentionally conducted based on several considerations. The data analisis method applied is descriptive analysis method by using questionnaires measured with Likert Scale. Based on the result of research, it can be concluded that satisfaction level of employees working for UD. Padma Sari is included in the category of Satisfied Enough for employees working for less than three years and more than three years, with achievement score of 64.35% for employees  working for more than three years and employees working for less than three years obtain the achievement score of 62.63%. Keywords : purposive, work satisfaction of employee, and likert scale
Keywords: purposive; work satisfaction of employee; likert scale